Paediatric tuberculosis: A decade-long experience in a tertiary care centre - Kamath, K Madhava; Giridhar, B H; Philip, Prijo (Indian Journal of Child Health, 2018)
Background: The World Health Organization estimates in 2013 revealed that up to 80,000 children die from tuberculosis (TB) each year and children account for over half a million new cases annually. The incidence of extrapulmonary TB (EPTB) is also on the rise. Aims: To study and note the total pediatric TB cases reported over a decade. Analysis of EPTB at the center was also attempted. Methods: Retrospective analysis of TB cases diagnosed during the past decade was attempted, through information registered in the hospital TB registry. Cases aged